Re-imagining Ukrainian Canadians : history, politics, and identity - Mochoruk, Jim, 1957-; Hinther, Rhonda L., 1974- (Canadian social history series., 2011)
Ukrainian immigrants to Canada have often been portrayed in history as sturdy pioneer farmers cultivating the virgin land of the Canadian west. The essays in this collection challenge this stereotype by examining the varied experiences of Ukrainian-Canadians in their day-to-day roles as writers, intellectuals, national organizers, working-class wage earners, and inhabitants of cities and towns. Throughout, the contributors remain dedicated to promoting the study of ethnic, hyphenated histories as major currents in mainstream Canadian history. Topics explored include Ukrainian-Canadian radicalism, the consequences of the Cold War for Ukrainians both at home and abroad, the creation and maintenance of ethnic memories, and community discord embodied by pro-Nazis, Communists, and criminals. Re-Imagining Ukrainian-Canadians uses new sources and non-traditional methods of analysis to answer unstudied and often controversial questions within the field.